Diskrepansi Pemanfaatan Ruang Publik Berdasarkan Teritori Ruang (Studi Kasus: Alun-alun Kota Klaten) - Anisza Ratnasari; Ratna Permatasari (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2019)
The town square, as one of the public open spaces in the urban areas which lately has decreased in number, is important for its existence to accommodate the social activities of urban communities. Klaten Square chosen as a location considering its main function as public open space. The facts indicate that it has undergone a transfer of function and has experienced abuse of use as a place of commercial activity by the informal sector. The purpose of this study is to map the location, behavior, time and activity of the discrepancy of the utilization of Klaten Square and what factors caused it to occur. The method is descriptive qualitative with data collection techniques through place-centered mapping and people-centered mapping. Theories regarding public space, behavior and territorial settings are used to analyze the data. The results of the study show that there’re discrepancies in the utilization of Klaten Square due to the diversity of users with various activities in certain places and at certain times. The results of this study can provide input to the local government to develop public spaces that are able to accommodate user activities and improve control and supervision of the regulations that have been set.